Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Teknologi - Achmad Junaedi Sitika; Amalia Khoiriyah; Anjar Dwi Ariani; Ayasis Aulia Hanif; Didah Maolida; Fitriani Dewi; Ghina Oktavia Nurbaeti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this article is to examine the development of Pai's curriculum in Indonesia in relation to 21st century competency needs. The method used in this study is a library study in which authors seek, collate, and analyze a variety of information from a variety of relevant sources. The beginning of the 21st century marked the rapid development of information and communication technology and the beginning of free competition between nations in all fields. As a result, student life today is different and much more complicated than it used to be. Indications for the results of this study include: Development of a PAI-based curriculum. In the era of Industry 4.0 revolution, Islamic religious education faces the challenge of destruction. Advances in digital technology have enabled everyone to access and quickly connect to all kinds of information through the Internet and it's innovations (the Internet of Things). This study uses a library survey method to collect and analyze library data. The research results show the adjustment of the Islamic education curriculum in the 4.0 era. The traditional blending and technology defense method is blended learning, and the content of things must adapt to the state and needs of skills in the 4.0 era, comprehensive assessment and shared responsibility (educational ecosystem). Educators had to convince her 4.0. Century needed compatibility. And infrastructure tools that adapt as technology evolves.